“Adipose-derived mesenchymal stem cell therapy for the management of female sexual dysfunction: Literature reviews and study design of a clinical trial” - Hoang, Van T.; Nguyen, Hoang-Phuong; Nguyen, Viet Nhan; Hoang, Duc M.; Nguyen, Tan-Sinh Thi; Nguyen Thanh, Liem (Frontiers in Cell and Developmental Biology, 2022)
Hormone imbalance and female sexual dysfunction immensely affect perimenopausal women's health and quality of life. Hormone therapy can improve female hormone deficiency, but long-term use increases the risk of cardiovascular disease and cancer. Therefore, it is necessary to develop a novel effective treatment to achieve long-term improvement in female general and sexual health. This study reviewed research on mesenchymal stromal cell/mesenchymal stem cell therapy to treat female reproductive diseases, including Asherman’s syndrome, premature ovarian failure/primary ovarian insufficiency, and vaginal atrophy. Our phase I clinical trial has demonstrated the safety of autologous adipose-derived stem cell (ASC) therapy for women and men with sexual hormone deficiency. We designed the first randomized controlled crossover phase II trial to investigate the safety and efficacy of autologous ASCs to treat female sexual dysfunction in perimenopausal women. Here, we introduce the rationale, trial design, and methodology of this clinical study. Because aging and metabolic diseases negatively impact the bioactivity of adult-derived MSCs, this study will employ ASCs cultured in physiological oxygen tension (5%) to cope with these challenges. A total of 130 perimenopausal women with sexual dysfunction will receive two intravenous infusions of autologous ASCs in a crossover design. The aims of the proposed study are to evaluate (1) the safety of cell infusion based on the frequency and severity of adverse events/serious adverse events during infusion and follow-up and (2) improvements in female sexual function assessed by the Female Sexual Function Index (FSFI), the Utian Quality of Life Scale (UQOL), and the levels of follicle-stimulating hormone (FSH) and estradiol. In addition, cellular aging biomarkers, including plasminogen activator inhibitor-1 (PAI-1), p16 and p21 expression in T cells and the inflammatory cytokine profile, will also be characterized. Overall, this study will provide essential insights into the effects and potential mechanisms of ASC therapy for perimenopausal women with sexual dysfunction. It also suggests direction and design strategies for future research.